ANALYSIS OF ANNUAL FLUCTUATION (2000-2022) IN TOMATO PRODUCTION IN PARAÍBA - Barbosa da Silva, João Henrique; Dias, Thiago Jardelino; Santos, João Paulo de Oliveira; da Silva, Ramon Freire; de Andrade, Francisco Hélio Alves; da Silva, Luís Karlos Pereira (Revista Científica da Faculdade de Educação e Meio Ambiente, 2025)
Tomato, a vegetable of significant importance due to its acceptability and nutritional value, has been cultivated and consumed globally since the 16th century, remaining a relevant crop in the agricultural context of Brazil and, particularly, in the state of Paraíba. This study's objective is to evaluate the productive dynamics of the tomato crop in Paraíba during the period between 2000 and 2022. Therefore, for this analysis, data were analyzed from the Municipal Agricultural Research information bank, made available by the Brazilian Institute of Geography and Statistics (IBGE). The Automatic Recovery System (SIDRA) was used to extract information pertinent to the planted area, harvested area, quantity produced, average yield and value of tomato production in that state. The results obtained revealed temporal variability in tomato production, particularly evident in fluctuations in the areas allocated to planting and harvesting. Due to the economic relevance of tomato cultivation for the state of Paraíba, it is necessary to stimulate and implement strategies aimed at improving the productivity of this crop.